Strategies for Improving Access to Cancer Services in Rural Communities: A Pre-implementation Study - Crabtree-Ide, Christina; Sevdalis, Nick; Bellohusen, Patricia; Constine, Louis S.; Fleming, Fergal; Holub, David; Rizvi, Irfan; Rodriguez, Jennifer; Shayne, Michelle; Termer, Nancy; Tomaszewski, Ken; Noyes, Katia (Frontiers in Health Services, 2022)
Background Implementation science is defined as the scientific study of methods and strategies that facilitate the uptake of evidence-based practice into regular use by practitioners. Failure of implementation is more common in resource-limited settings and may contribute to health disparities between rural and urban communities. In this pre-implementation study, we aimed to (1) evaluate barriers and facilitators for implementation of guideline-concordant healthcare services for cancer patients in rural communities in Upstate New York and (2) identify key strategies for successful implementation of cancer services and supportive programs in resource-poor settings. Methods The mixed methods study was guided by the Consolidated Framework for Implementation Research (CFIR). Using engagement approaches from Community-Based Participatory Research, we collected qualitative and quantitative data to assess barriers and facilitators to implementation of rural cancer survivorship services (three focus groups, n = 43, survey n = 120). Information was collected using both in-person and web-based approaches and assessed attitude and preferences for various models of cancer care organization and delivery in rural communities. Stakeholders included cancer survivors, their families and caregivers, local public services administrators, health providers, and allied health-care professionals from rural and remote communities in Upstate New York. Data was analyzed using grounded theory. Results Responders reported preferences for cross-region team-based cancer care delivery and emphasized the importance of connecting local providers with cancer care networks and multidisciplinary teams at large urban cancer centers. The main reported barriers to rural cancer program implementation included regional variation in infrastructure and services delivery practices, inadequate number of providers/specialists, lack of integration among oncology, primary care and supportive services within the regions, and misalignment between clinical guideline recommendations and current reimbursement policies. Conclusions Our findings revealed a unique combination of community, socio-economic, financial, and workforce barriers to implementation of guideline-concordant healthcare services for cancer patients in rural communities. One strategy to overcome these barriers is to improve provider cross-region collaboration and care coordination by means of teamwork and facilitation. Augmenting implementation framework with provider team-building strategies across and within regions could improve rural provider confidence and performance, minimize chances of implementation failure, and improve continuity of care for cancer patients living in rural areas.